Preparation method and application of highly water-resistant and highly transparent biodegradable resin
By introducing neopentyl glycol into PBAT and copolymerizing with modified PPC, the shortcomings of existing degradable resins in water barrier properties and transparency are solved, and a degradable resin with high water barrier, high transparency and high elongation of break is achieved, which is suitable for a variety of application needs.
Patent Information
- Application Number
- CN202310000492.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-03
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-01-03
AI Technical Summary
The existing degradable resins have shortcomings in water barrier properties and transparency, and it is difficult to meet the needs of high water and gas barrier properties such as food preservation.
By introducing a small amount of neopentyl glycol with hydrophobic groups during the PBAT polymerization process, the hydrophobicity of the chain segment is improved and copolymerized with terephthalic acid-modified PPC, a degradable resin with high water barrier, high transparency and high elongation of break is obtained.
The film has achieved high water resistance performance (water vapor permeability coefficient is less than 300 10-13g·m/m2·s·Pa), high transparency (haze is less than 10%) and high elongation of break (700-1000%), and is suitable for various transparent biodegradable products.
Smart Images

Figure BDA0004034258080000101
Abstract
Description
Technical Field
[0001] The invention relates to a degradable resin, and in particular to a preparation method and application of a highly water-resistant and highly transparent degradable resin. Background Art
[0002] In recent years, "white pollution" and microplastics have attracted great attention from all over the world, and the biodegradable plastic industry has become increasingly popular. Polybutylene terephthalate (PBAT) combines the degradation properties of aliphatic polyesters and the mechanical properties of aromatic polyesters, has good ductility and elongation at break, and has been widely used. However, compared with traditional materials such as polyethylene terephthalate resin (PET), PBAT film has poor water barrier properties, and its high water vapor permeability makes it difficult to meet the needs of food preservation. Its application is limited in areas such as agricultural film, straws, liquid packaging bags, liquid packaging bottles, fast food boxes, and pharmaceutical packaging that require high water and gas barriers. Polymethylethylene carbonate (PPC) has good water barrier properties among biodegradable plastics, but its elongation at break is less than 10%. In the process of using PPC alone to prepare films, due to its insufficient toughness, unstable film bubbles, and occasional film breakage problems, it seriously affects production efficiency. Therefore, many patents complement the advantages and disadvantages of several biodegradable plastics by blending and modifying them. For example, patent CN110628185B provides a polybutylene terephthalate-adipate / polymethyl ethylene carbonate fully biodegradable film and its preparation method, by blending PBAT with maleic anhydride or succinic anhydride modified PPC and other additives to obtain a degradable film with the advantages of high tear strength, good elongation at break, good barrier properties, good biodegradability, and uniform tensile properties in all directions. Patent CN113248888A provides a highly permeable and water-resistant toughened fully degradable environmentally friendly film, which is made by blending and modifying PLA, PPC and PBAT in proportion under the action of additives, and realizes the complementary advantages and disadvantages between the soft, highly tensile PBAT and the highly water-resistant PPC and transparent PLA. However, the film modified by blending has poor compatibility between the two phases, and the phase morphology will be uneven during the casting or film blowing process, and the mechanical properties of the film will be affected to a certain extent, so it is also necessary to add plasticizers, lubricants and other additives to improve compatibility. Summary of the invention
[0003] In order to solve the above technical problems, the present invention proposes a preparation method and application of a highly water-resistant and highly transparent degradable resin. The present invention has found through research that in the PBAT polymerization process, by introducing a small amount of neopentyl glycol with a hydrophobic group to improve the hydrophobicity of the chain segment, and then copolymerizing with terephthalic acid-modified PPC, a highly water-resistant, highly transparent and high elongation-at-break degradable resin can be obtained without adding other additives.
[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0005] A method for preparing a highly water-resistant and highly transparent biodegradable resin comprises the following steps:
[0006] 1) mixing adipic acid, terephthalic acid, 1,4-butanediol and neopentyl glycol to react and polymerize to obtain modified PBAT oligomer A;
[0007] 2) Propylene oxide and terephthalic acid are mixed in the presence of catalyst A, and a certain pressure of CO is introduced. 2 Reaction is carried out to polymerize and obtain modified PPC oligomer B;
[0008] 3) The modified PBAT oligomer A, the modified PPC oligomer B and the branching agent are mixed, the catalyst B is added, and vacuum polycondensation is performed to obtain the degradable resin.
[0009] As a preferred embodiment, in step 1), the molar ratio of the sum of the added amounts of 1,4-butanediol and neopentyl glycol to the sum of the added amounts of adipic acid and terephthalic acid is 1.2-1.5:1; and / or,
[0010] The molar ratio of 1,4-butanediol to neopentyl glycol is 6-9:1; and / or,
[0011] The molar ratio of adipic acid to terephthalic acid is 1.2-1.8:1.
[0012] As a preferred embodiment, the reaction conditions in step 1) are esterification reaction at 190-230° C. for 2-3 h.
[0013] As a preferred embodiment, the catalyst A is a zinc catalyst, and the addition amount of the catalyst A is 100-200 ppm of the mass of terephthalic acid, calculated on the basis of the mass of the zinc element;
[0014] Preferably, the catalyst A is selected from any one or more of zinc oxide, zinc carbonate, zinc hydroxide, diethyl zinc, and zinc valerate.
[0015] As a preferred embodiment, in step 2), the molar ratio of propylene oxide to terephthalic acid is 1.2-1.6:1.
[0016] As a preferred embodiment, the reaction conditions in step 2) are: at 60-70°C, 0.5-1.5 MPa CO 2 The copolymerization reaction was carried out for 2-4h under the conditions.
[0017] As a preferred embodiment, in step 3), the mass ratio of the modified PBAT oligomer A to the modified PPC oligomer B is 1-5:1; and / or,
[0018] In step 3), the amount of the branching agent added is 0.1-0.3% of the total mass of the modified PBAT oligomer A and the modified PPC oligomer B;
[0019] Preferably, the branching agent is selected from diglycidyl ethers, selected from any one or more of polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, and 1,6-hexanediol diglycidyl ether.
[0020] As a preferred embodiment, in step 3), catalyst B is a titanium catalyst, and the amount of catalyst B added is 200-400 ppm of the total mass of modified PBAT oligomer A and modified PPC oligomer B, calculated on the basis of the mass of titanium element;
[0021] Preferably, the catalyst B is selected from any one or more of tetrabutyl titanate, tetraisopropyl titanate, and tetraisooctyl titanate.
[0022] As a preferred embodiment, the reaction conditions in step 3) are: 0-200 Pa, 230-240° C., and polycondensation reaction for 3-4 hours.
[0023] As a preferred embodiment, the number average molecular weight of the modified PBAT oligomer A is 2000-4000 g / mol; and / or
[0024] The number average molecular weight of the modified PPC oligomer B is 2000-4000 g / mol; and / or
[0025] The number average molecular weight of the degradable resin is 3×10 5 -6×10 5 g / mol, and the melting point at 190°C and 2.16 kg is 2-8 g / 10 min.
[0026] The reaction pressure in the present invention refers to absolute pressure unless otherwise specified.
[0027] In the preparation process of PBAT resin, the present invention first introduces a certain proportion of neopentyl glycol with hydrophobic groups, which can effectively improve the hydrophobicity of the molecular chain; secondly, copolymerization with PPC, which is recognized as having good water-blocking properties in degradable plastics, can further improve its water-blocking properties. Since PPC itself has the problem of insufficient toughness, PTA is added to copolymerize and modify PPC; in addition, since the structural regularity of the chain segment is destroyed, the crystallinity of PBAT is reduced, which greatly improves the transparency and tensile properties of the product. Therefore, by copolymerizing the modified PBAT oligomer A and the modified PPC oligomer B through the preparation method provided by the present invention, various transparent biodegradable products suitable for high water-blocking requirements can be obtained.
[0028] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0029] The present invention introduces hydrophobic groups during the synthesis of PBAT and copolymerizes it with modified PPC, so that the water vapor permeability coefficient of the film prepared by the present invention can be lower than 300 10 -13 g·m / m 2 ·s·Pa, the film haze is less than 10%, and the film elongation at break is between 700-1000%, which can meet the production of various transparent biodegradable products with high water resistance requirements. DETAILED DESCRIPTION
[0030] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0031] In the following embodiments of the present invention, 1,4-butanediol, adipic acid, terephthalic acid, neopentyl glycol, propylene oxide, zinc oxide, zinc carbonate, zinc hydroxide, diethyl zinc, zinc valerate, tetrabutyl titanate, tetraisopropyl titanate, tetraisooctyl titanate, polyethylene glycol diglycidyl ether (brand: XY205), polypropylene glycol diglycidyl ether (brand: XY207), neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether are all commercially available, and the others are all common commercially available raw materials unless otherwise specified.
[0032] In the following embodiments of the present invention, the main test methods involved are as follows:
[0033] a) Relative molecular weight: Waters gel chromatography was used to test the relative molecular weight of the polymer, with chloroform as the mobile phase, an elution rate of 1 mL / min, a temperature of 40°C, and a narrow distribution polystyrene as the standard sample;
[0034] b) Melt index: measured by a German GOTTFERT melt flow index tester at 190°C and 2.16 kg for melt mass flow rate (MFR);
[0035] c) Water vapor transmission coefficient (WVP) test: The equipment is WB-31 water vapor transmission instrument, referring to the standard GB / T 1037-1988, and the cup method is used to test the water vapor barrier properties of the film samples. The test temperature is 38°C, the relative humidity is 90% RH, the pressure is 0.1MPa, and the test time is 40h. The water vapor transmission mass per unit volume per unit area is recorded to calculate the water vapor transmission coefficient;
[0036] d) Haze: A haze meter (BYK, 4775) was used for testing. The test was performed according to standard GB / T 2410-2008. The haze of the film sample was recorded and the average value was taken for five times.
[0037] e) Tensile properties: A universal tensile testing machine was used for the test. Referring to the standard ISO 527-3:2018, the film sample was first cut into (150 mm × 15 mm) rectangular strips with a cutter, and then clamped on a single-column tensile testing machine (Zwick, Z0.5) with a gauge length of 50 mm. The tensile properties were tested using a tensile force of 200 N at a speed of 500 mm / min. The data was transmitted to the computer through a sensor, and the average value was taken after five measurements.
[0038] [Example 1]
[0039] The biodegradable resin was prepared as follows:
[0040] 175.2 g of adipic acid, 166 g of terephthalic acid, 204.3 g of 1,4-butanediol, and 38.5 g of neopentyl glycol were mixed and reacted at 190° C. under normal pressure for 2 h to obtain a modified PBAT oligomer A with a molecular weight Mn of 2025 g / mol;
[0041] (2) 69.7 g of propylene oxide, 166 g of terephthalic acid, and 0.021 g of zinc oxide were mixed, 0.5 MPa of carbon dioxide was introduced, the temperature was raised to 60° C., and the reaction was carried out under a slight positive pressure for 2.0 h to obtain a modified PPC oligomer B with a molecular weight Mn of 2102 g / mol;
[0042] (3) 100 g of modified PBAT oligomer A was mixed with 100 g of modified PPC oligomer B, 0.2 g of polyethylene glycol diglycidyl ether and 0.285 g of tetrabutyl titanate were added, and the mixture was subjected to polycondensation reaction at 200 Pa and 230 °C for 3.0 h to obtain a biodegradable resin A with a molecular weight of 3.2 × 10 5 g / mol.
[0043] [Example 2]
[0044] The biodegradable resin was prepared as follows:
[0045] (1) 189.8 g of adipic acid, 166 g of terephthalic acid, 213.3 g of 1,4-butanediol, and 40.6 g of neopentyl glycol were mixed and reacted at 195° C. under normal pressure for 2.2 h to obtain a modified PBAT oligomer A with a molecular weight Mn of 2315 g / mol;
[0046] (2) 75.5 g of propylene oxide, 166 g of terephthalic acid, and 0.038 g of zinc carbonate were mixed, 0.6 MPa of carbon dioxide was introduced, the temperature was raised to 60° C., and the reaction was carried out under a slight positive pressure for 2.4 h to obtain a modified PPC oligomer B with a molecular weight Mn of 2320 g / mol;
[0047] (3) 200 g of modified PBAT oligomer A was mixed with 100 g of modified PPC oligomer B, 0.45 g of polyethylene glycol diglycidyl ether and 0.533 g of tetrabutyl titanate were added, and the polycondensation reaction was carried out at 200 Pa and 230 ° C for 3.2 h to obtain a biodegradable resin B with a molecular weight Mn of 3.7×10 5 g / mol.
[0048] [Example 3]
[0049] The biodegradable resin was prepared as follows:
[0050] (1) 204.4 g of adipic acid, 166 g of terephthalic acid, 245.7 g of 1,4-butanediol, and 40.6 g of neopentyl glycol were mixed and reacted at 200° C. under normal pressure for 2.4 h to obtain a modified PBAT oligomer A with a molecular weight Mn of 2565 g / mol;
[0051] (2) 81.3 g of propylene oxide, 166 g of terephthalic acid, and 0.035 g of zinc hydroxide were mixed, 0.8 MPa of carbon dioxide was introduced, the temperature was raised to 65° C., and the reaction was carried out under a slight positive pressure for 2.8 h to obtain a modified PPC oligomer B with a molecular weight Mn of 2566 g / mol;
[0052] (3) 250 g of modified PBAT oligomer A and 100 g of modified PPC oligomer B were mixed, 0.7 g of polypropylene glycol diglycidyl ether and 0.623 g of tetraisopropyl titanate were added, and the polycondensation reaction was carried out at 150 Pa and 235 ° C for 3.4 h to obtain a biodegradable resin C with a molecular weight Mn of 4.0×10 5 g / mol.
[0053] [Example 4]
[0054] The biodegradable resin was prepared as follows:
[0055] (1) 219.0 g of adipic acid, 166 g of terephthalic acid, 255.6 g of 1,4-butanediol, and 42.7 g of neopentyl glycol were mixed and reacted at 205° C. under normal pressure for 2.6 h to obtain a modified PBAT oligomer A with a molecular weight Mn of 2778 g / mol;
[0056] (2) 81.3 g of propylene oxide, 166 g of terephthalic acid, and 0.050 g of diethyl zinc were mixed, 1.0 MPa of carbon dioxide was introduced, the temperature was raised to 65° C., and the reaction was carried out under a slight positive pressure for 3.0 h to obtain a modified PPC oligomer B with a molecular weight Mn of 2855 g / mol;
[0057] (3) 300 g of modified PBAT oligomer A and 100 g of modified PPC oligomer B were mixed, 0.8 g of polypropylene glycol diglycidyl ether and 0.712 g of tetraisopropyl titanate were added, and the polycondensation reaction was carried out at 150 Pa and 235 ° C for 3.6 h to obtain a biodegradable resin D with a molecular weight Mn of 5.0×10 5 g / mol.
[0058] [Example 5]
[0059] The biodegradable resin was prepared as follows:
[0060] (1) 233.6 g of adipic acid, 166 g of terephthalic acid, 291.6 g of 1,4-butanediol, and 41.7 g of neopentyl glycol were mixed and reacted at 210° C. under normal pressure for 2.8 h to obtain a modified PBAT oligomer A with a molecular weight Mn of 3021 g / mol;
[0061] (2) 87.1 g of propylene oxide, 166 g of terephthalic acid, and 0.116 g of zinc valerate were mixed, 1.2 MPa of carbon dioxide was introduced, the temperature was raised to 70° C., and the reaction was carried out under a slight positive pressure for 3.4 h to obtain a modified PPC oligomer B with a molecular weight Mn of 2756 g / mol;
[0062] (3) 400 g of modified PBAT oligomer A was mixed with 100 g of modified PPC oligomer B, 1.25 g of neopentyl glycol diglycidyl ether and 2.065 g of tetraethylhexyl titanate were added, and the polycondensation reaction was carried out at 100 Pa and 240 ° C for 3.8 h to obtain a biodegradable resin E with a molecular weight Mn of 5.3×10 5 g / mol.
[0063] [Example 6]
[0064] The biodegradable resin was prepared as follows:
[0065] (1) 248.2 g of adipic acid, 166 g of terephthalic acid, 327.6 g of 1,4-butanediol, and 42.7 g of neopentyl glycol were mixed and reacted at 220° C. under normal pressure for 3.0 h to obtain a modified PBAT oligomer A with a molecular weight Mn of 3588 g / mol;
[0066] (2) 92.9 g of propylene oxide, 166 g of terephthalic acid, and 0.056 g of diethyl zinc were mixed, 1.4 MPa of carbon dioxide was introduced, the temperature was raised to 70° C., and the reaction was carried out under a slight positive pressure for 3.8 h to obtain a modified PPC oligomer B with a molecular weight Mn of 3547 g / mol;
[0067] (3) 450 g of modified PBAT oligomer A and 100 g of modified PPC oligomer B were mixed, 1.65 g of neopentyl glycol diglycidyl ether and 2.595 g of tetraethyl hexyl titanate were added, and the polycondensation reaction was carried out at 50 Pa and 240 ° C for 4.0 h to obtain a biodegradable resin F with a molecular weight Mn of 5.7×10 5 g / mol.
[0068] [Example 7]
[0069] The biodegradable resin was prepared as follows:
[0070] (1) 262.8 g of adipic acid, 166 g of terephthalic acid, 340.2 g of 1,4-butanediol, and 43.7 g of neopentyl glycol were mixed and reacted at 230° C. under normal pressure for 3.0 h to obtain a modified PBAT oligomer A with a molecular weight Mn of 3956 g / mol;
[0071] (2) 92.9 g of propylene oxide, 166 g of terephthalic acid, and 0.063 g of diethyl zinc were mixed, 1.5 MPa of carbon dioxide was introduced, the temperature was raised to 70° C., and the reaction was carried out under a slight positive pressure for 4.0 h to obtain a modified PPC oligomer B with a molecular weight Mn of 3866 g / mol;
[0072] (3) 500 g of modified PBAT oligomer A and 100 g of modified PPC oligomer B were mixed, 1.8 g of 1,6-hexanediol diglycidyl ether and 1.706 g of tetrabutyl titanate were added, and the polycondensation reaction was carried out at 20 Pa and 240 ° C for 4.0 h to obtain a biodegradable resin G with a molecular weight Mn of 5.9×10 5 g / mol.
[0073] [Comparative Example 1]
[0074] Degradable resin H was prepared in substantially the same manner as in Example 7, except that no neopentyl glycol was added in step (1).
[0075] [Comparative Example 2]
[0076] Degradable resin I was prepared in substantially the same manner as in Example 7, except that terephthalic acid was not added in step (2).
[0077] [Comparative Example 3]
[0078] Prepare the mixed biodegradable resin as follows:
[0079] (1) 262.8 g of adipic acid, 166 g of terephthalic acid, and 340.2 g of 1,4-butanediol were mixed and reacted at 230°C under normal pressure for 2.5 h. Then, 0.8 g of 1,6-hexanediol diglycidyl ether and 0.71 g of tetrabutyl titanate were added and polycondensed at 50 Pa and 235°C for 3.5 h to obtain a PBAT polymer with a molecular weight Mn of 5.2×10 5 g / mol.
[0080] (2) 92.9 g of propylene oxide and 0.063 g of diethyl zinc were mixed, 5.0 MPa of carbon dioxide was introduced, the temperature was raised to 70 °C, and the reaction was carried out under positive pressure for 40 h to obtain PPC polymer B with a molecular weight Mn of 4.6 × 10 5 g / mol.
[0081] (3) PBAT polymer and PPC polymer were blended at a mass ratio of 4:1, melt-extruded and granulated in a twin-screw extruder at 190° C. to prepare a biodegradable resin J.
[0082] The biodegradable resins prepared in the embodiments and comparative examples were respectively formed into films with a film width of 25 cm and a single-layer film thickness of about (25±3) μm by a film blowing machine, and relevant performance tests were performed. The results are shown in Table 1.
[0083] Table 1. Performance test results
[0084]
[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a highly water-resistant and highly transparent biodegradable resin, characterized in that: The following steps are involved: 1) mixing adipic acid, terephthalic acid, 1,4-butanediol and neopentyl glycol to react and polymerize to obtain modified PBAT oligomer A; 2) mixing propylene oxide and terephthalic acid in the presence of catalyst A, and introducing CO2 to react, thereby polymerizing to obtain modified PPC oligomer B; 3) mixing the modified PBAT oligomer A, the modified PPC oligomer B and the branching agent, adding the catalyst B, and performing vacuum polycondensation to obtain the degradable resin; In step 1), the molar ratio of the sum of the added amounts of 1,4-butanediol and neopentyl glycol to the sum of the added amounts of adipic acid and terephthalic acid is 1.2-1.5:1; The molar ratio of 1,4-butanediol to neopentyl glycol is 6-9:1; The molar ratio of adipic acid to terephthalic acid is 1.2-1.8:1; In step 2), the molar ratio of propylene oxide to terephthalic acid is 1.2-1.6:1; In step 3), the mass ratio of modified PBAT oligomer A to modified PPC oligomer B is 1-5:
1.
2. The method for preparing a highly water-resistant and highly transparent biodegradable resin according to claim 1, characterized in that: The reaction conditions in step 1) are esterification reaction at 190-230° C. for 2-3 hours.
3. The method for preparing a highly water-resistant and highly transparent biodegradable resin according to claim 1, characterized in that: The catalyst A is a zinc catalyst. The amount of catalyst A added is 100-200 ppm of the mass of terephthalic acid, calculated on the basis of the mass of zinc element.
4. The method for preparing a highly water-resistant and highly transparent biodegradable resin according to claim 3, characterized in that: Catalyst A is selected from any one or more of zinc oxide, zinc carbonate, zinc hydroxide, diethyl zinc, and zinc valerate.
5. The method for preparing a highly water-resistant and highly transparent biodegradable resin according to claim 1, characterized in that: The reaction conditions in step 2) are: copolymerization reaction at 60-70°C with 0.5-1.5 MPa CO2 introduced for 2-4 hours.
6. The method for preparing a highly water-resistant and highly transparent biodegradable resin according to claim 1, characterized in that: In step 3), the amount of the branching agent added is 0.1-0.3% of the total mass of the modified PBAT oligomer A and the modified PPC oligomer B.
7. The method for preparing a highly water-resistant and highly transparent biodegradable resin according to claim 6, characterized in that: The branching agent is selected from diglycidyl ethers.
8. The method for preparing a highly water-resistant and highly transparent biodegradable resin according to claim 7, characterized in that: The branching agent is selected from any one or more of polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, and 1,6-hexanediol diglycidyl ether.
9. The method for preparing a highly water-resistant and highly transparent biodegradable resin according to claim 6, characterized in that: In step 3), catalyst B is a titanium-based catalyst, and the amount of catalyst B added is 200-400 ppm of the total mass of the modified PBAT oligomer A and the modified PPC oligomer B, calculated on the basis of the mass of the titanium element.
10. The method for preparing a highly water-resistant and highly transparent biodegradable resin according to claim 9, characterized in that: The catalyst B is selected from any one or more of tetrabutyl titanate, tetraisopropyl titanate, and tetraisooctyl titanate.
11. The method for preparing a highly water-resistant and highly transparent biodegradable resin according to any one of claims 6 to 10, characterized in that: The reaction conditions in step 3) are: 0-200 Pa, 230-240° C., and polycondensation for 3-4 hours.
12. The method for preparing a highly water-resistant and highly transparent biodegradable resin according to any one of claims 1 to 10, characterized in that: The number average molecular weight of the modified PBAT oligomer A is 2000-4000 g / mol; and / or The number average molecular weight of the modified PPC oligomer B is 2000-4000 g / mol; and / or The number average molecular weight of the degradable resin is 3×10 5 -6×10 5 g / mol, and the melting point at 190°C and 2.16 kg is 2-8 g / 10 min.
Citation Information
Patent Citations
A fully biodegradable polybutylene terephthalate / polymethyl ethylene carbonate film and its preparation method
CN110628185B
High-permeability water-blocking toughened fully-degradable environment-friendly film and preparation method thereof
CN113248888A
Copolymer of aliphatic poly propylene carbonate-aromatic polyester and method for preparing same
CN101735435A
Biodegradable multilayer material with adjustable gas transmission rate and preparation method and applications thereof
CN104691067A